2005
DOI: 10.21273/hortsci.40.6.1731
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Cultivar Effects on Anthocyanin and Chlorophyll b Concentrations in Three Related Lollo Rosso Lettuce Cultivars

Abstract: Pigment concentrations in leaf tissue affect the visual and nutritional value-based indices of lettuce crop quality. To better discern the independent and interactive effects of temperature and cultivar on anthocyanin and chlorophyll b concentrations, three closely related Lolla Rosso lettuce cultivars (`Lotto', `Valeria', and `Impuls'), varying primarily in the number of genes controlling anthocyanin concentrations, were subjected to different air temperatures in controlled environments. Fifteen-day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…Hence, the breeders selecting for dark red color (high RAC) may consider temporarily subjecting lettuce plants to low temperatures where differences among genotypes are likely to be more pronounced (assuming that the pattern of changes in pigments is the same as in our study). These results are somewhat unexpected, because several previous studies reported that low temperatures lead to increased anthocyanin production in lettuce (Gazula et al, 2005, 2007; Boo et al, 2011; Chon et al, 2012; Becker et al, 2014a). However, when the regulation of anthocyanin biosynthesis [quantified as cyanidin-3- O -( 6 ″-malonyl)-glucoside] was compared in three cultivars, a substantial difference in their response to varying temperatures was detected.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hence, the breeders selecting for dark red color (high RAC) may consider temporarily subjecting lettuce plants to low temperatures where differences among genotypes are likely to be more pronounced (assuming that the pattern of changes in pigments is the same as in our study). These results are somewhat unexpected, because several previous studies reported that low temperatures lead to increased anthocyanin production in lettuce (Gazula et al, 2005, 2007; Boo et al, 2011; Chon et al, 2012; Becker et al, 2014a). However, when the regulation of anthocyanin biosynthesis [quantified as cyanidin-3- O -( 6 ″-malonyl)-glucoside] was compared in three cultivars, a substantial difference in their response to varying temperatures was detected.…”
Section: Discussionmentioning
confidence: 72%
“…Reduced concentrations of chlorophyll and anthocyanin have been observed in lettuce grown at supra-optimal temperatures (Gazula et al, 2005; Chon et al, 2012). These changes in the chlorophyll content are at odds with our observations that show overall increases in RCC with growing temperature ( Figures 7, 8 , and 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression of PAL, chalcone isomerase and enzymes related to anthocyanin biosynthesis increased under lower temperature (Gazula et al . (). Mori et al .…”
Section: Resultsmentioning
confidence: 97%
“…Benoit et al [18] found that plastic-covered and uncovered lettuce plants contained 11.0 and 16.6 μg carotene per g fresh wt, respectively. Increasing temperatures from 20 o C to 30 o C reduced anthocyanin (cyanidin) and chlorophyll b concentrations in three red leaf lettuce cultivars [19]. Carotene levels of butterhead lettuce produced by various cultivation methods ranged from 1,360 to 3,190 μg/100 g fresh wt in soil-grown samples and from 1,810 to 2,760 μg/100 g in hydroponically grown samples [20].…”
Section: Ii2 Environmental Influencementioning
confidence: 99%